Ipoh Hainan Chicken Rice / Nor Shahril Aidil Nor Eddie - Nor Eddie, Nor Shahril Aidil (2020)
An eatery that located at jalan raja musa aziz in Ipoh Town, Perak. known for hainanese chicken rice and dishes across east asia countries such as japanese bento crab meat, and mango salad with halal quality.